FACTORS AND MOTIVES FOR THE SPIN-OFF PROCESS - Igor B. Khmelev; Sergei V. Kruglov (Статистика и экономика, 2016)
This article is about the factors that encourage managers to use spin offs as a restructuring tool, and about the main motives of spin-off transactions. Attention is focused on the nature of spin-offs. There is a classification of the driving factors of spin-offs from the theoretical viewpoint and the degree of this question elaboration in economic literature. Four factors are marked: industrial, life cycle, company size and support of the parent company. The basic spin-off motives are pointed in this article.